1960
DOI: 10.1136/oem.17.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Renal Lesions in Experimental Cadmium Poisoning

Abstract: A series of controlled experiments was carried out on rats to study the effects on the kidneys of the repeated administration of small doses of cadmium for periods of up to 12 months. Renal lesions consisting essentially of tubular atrophy and interstitial fibrosis were produced, and the evidence that these lesions were due solely to cadmium is discussed. No similar lesions occurred in a series of control animals, litter mates of the experimental animals. The lesions were shown to be reproducible in two prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Such a time lag was not pointed out in previous papers (Axelsson and Piscator, 1966a;Bonnell et al, 1960;Yoshikawa, 1979), in which Cd accumulation was shown to reach its maximum or plateau level in both liver and kidney at a time after long-term Cd exposure. Nevertheless,.the time lag indicates that the second sharp increase in urinary excretion of Cd in stage III is related to the decline of hepatic Cd.…”
Section: Discussionmentioning
confidence: 51%
“…Such a time lag was not pointed out in previous papers (Axelsson and Piscator, 1966a;Bonnell et al, 1960;Yoshikawa, 1979), in which Cd accumulation was shown to reach its maximum or plateau level in both liver and kidney at a time after long-term Cd exposure. Nevertheless,.the time lag indicates that the second sharp increase in urinary excretion of Cd in stage III is related to the decline of hepatic Cd.…”
Section: Discussionmentioning
confidence: 51%
“…The continuous exposure resulted in a plateau and a subsequent decline (Axelsson and Piscator 1966). In rat, a linear increase was observed until the equilibrium states of 200-300 and 350 μg/g wet tissue weight in kidney and liver, respectively, after a 0.75 mg/kg intraperitoneal injection of Cd silver nitrate (Bonnell et al 1960). Similar correlations and regressions between Cd contents in liver and kidney were observed in wildlife such as fulmar (Flumarus glacialis ) and southern fulmar (Flumarus glacialoides) (Norheim 1987) oystercatcher (Haematopus ostralegus) and great skua (Chatharacta skua) (Hutton 1981), and ducks (Mochizuki et al 2002).…”
Section: Discussionmentioning
confidence: 89%
“…In Cd-exposed people, the chronic toxicity such as renal dysfunction will appear only after a long lag period of several years, and when a critical concentration of renal Cd is reached (8,9). It is known that there is a gradual mobilization of Cd from liver to kidney and the major critical organ in chronic Cd toxicity is the kidney (10)(11)(12). Therefore, it is important to consider all the factors involved in the renal deposition of Cd to develop an effective chelation therapy for Cd and to prevent the Cd induced renal disease.…”
mentioning
confidence: 99%